Los fundamentos técnicos del voleibol en la iniciación deportiva de los estudiantes de octavo y noveno año de la escuela de educación básica “Dr. Daniel Rodas Bustamante” de la ciudad de Loja, período 2014-2015 - Taday Armijos, Freddy Fernando (2016)
This research has as its theme: VOLLEYBALL TECHNICAL FOUNDATIONS IN SPORTS INITIATION OF STUDENTS OF EIGHTH AND NINTH YEAR OF BASIC SCHOOL EDUCATION "DR. DANIEL RODAS BUSTAMANTE" CITY OF LOJA, 2014-2015. This project focuses on research on how they affect the processes of learning of the technical fundamentals of volleyball on the sports initiation stage, the goal is aimed at: determining an exercise program to improve the process of learning of the technical fundamentals of volleyball, it should be noted that volleyball is a sport played by two teams on a field divided by a network whose aim is to send the ball over the net in order to make it touch the floor of the opponent's court and prevent the opponent to do the same in the half and sports initiation is the beginning of the individual in the sport for the acquisition of knowledge and implementation capacity practice of sport during this process it is considered different methods and techniques, including the scientific method, inductive-deductive, analytic-synthetic, descriptive and statistical modeling techniques such as survey and initial and final test at 36 students applied. With the full arsenal of information implementation of the instruments it was achieved positive results by improving teaching and learning processes and thus properly execute the technical fundamentals of volleyball improving 100% of students that can demonstrate they are in the process mastering the basics and conclude the study to characterize the educational process, and educational psychology, which made it possible to determine a set of components for students to cope better in sports and a recommendation to run an exercise program for the process of learning of the technical fundamentals of volleyball pedagogically designed taking into account the characteristics of sports initiation stage